Naringin Mediates Adult Hippocampal Neurogenesis for Antidepression via Activating CREB Signaling - Gao, Chong; Wu, Meiling; Du, Qiaohui; Deng, Jiagang; Shen, Jiangang (Frontiers in Cell and Developmental Biology, 2022)
Brain-derived neurotrophic factor/tropomycin receptor kinase B/cAMP response element-binding protein(BDNF/TrkB/CREB) signaling pathway becomes a critical therapeutic target for inducing adult hippocampal neurogenesis and antidepressant therapy. In the present study, we tested the hypothesis that naringin, a natural medicinal compound, could promote adult hippocampal neurogenesis and improve depressive like behaviors via regulating BDNF/TrkB/CREB signaling pathway. We first investigated the effects of naringin on promoting adult hippocampal neurogenesis in both normal and chronic corticosterone (CORT) induced depressive mice. Under physiological condition, naringin treatment enhanced the proliferation of neural stem/progenitor cells (NSPCs) and accelerated neuronal differentiation. In CORT-induced depression mouse model, naringin treatment promoted neuronal differentiation and maturation of NSPCs for hippocampal neurogenesis. Force swim test, tail suspension test and open field test confirmed the naringin’s antidepressant and anxiolytic effects. Co-treatment of temozolomide (TMZ), an neurogenic inhibitor, abolished these antidepressant and anxiolytic effects. Meanwhile, naringin treatment increased the phosphorylation of cAMP response element binding protein (CREB) but had no effect on the expression of BDNF and the phosphorylation of TrkB in the hippocampus of CORT-induced depressive mice . Co-treatment of CREB inhibitor 666-15, rather than TrkB inhibitor Cyc-B, abolished the neurogenesis-promoting and anti-depressant effects of naringin. Taken together, naringin has antidepressant and anxiolytic effects and the underlying mechanisms could be attributed to enhance hippocampal neurogenesis via activating CREB signaling.